Current Awareness and Use of the Strain Echocardiography in Routine Clinical Practices: Result of a Nationwide Survey in Korea - Lee, Ju-Hee (J Cardiovasc Ultrasound, 2017)
BACKGROUND: Because conventional echocardiographic parameters have several limitations, strain echocardiography has often been introduced in clinical practice. However, there are also obstacles in using it in clinical practice. Therefore, we wanted to find the current status of awareness on using strain echocardiography in Korea. METHODS: We conducted a nationwide survey to evaluate current use and awareness of strain echocardiography from the members of the Korean Society of Echocardiography. RESULTS: We gathered total 321 questionnaires from 25 cardiology centers in Korea. All participants were able to perform or interpret echocardiographic examinations. All participating institutions performed strain echocardiography. Most of our study participants (97%) were aware of speckle tracking echocardiography and 185 (58%) performed it for clinical and research purposes. Two-dimensional strain echocardiography was the most commonly used modality and left ventricle (LV) was the most commonly used cardiac chamber (99%) for clinical purposes. Most of the participants (89%) did not think LV strain can replace LV ejection fraction (LVEF) in their clinical practice. The common reasons for not performing routine use of strain echocardiography was diversity of strain measurements and lack of normal reference value. Many participants had a favorable view of the future of strain echocardiography. CONCLUSION: Most of our study participants were aware of strain echocardiography, and all institutions performed strain echocardiography for clinical and research purposes. However, they did not think the LV strain values could replace LVEF. The diversity of strain measurements and lack of normal reference values were common reasons for not using strain echocardiography in clinical practice.